Comparative Evaluation of Salivary Neopterin Levels and Its Effects to Periodontal Therapy in Pre- and Post-Menopausal Women - Prasanna, Jammula Surya; Sumadhura, Chinta; Karunakar, Parupalli; Rohini, Naineni (Journal of menopausal medicine, 2017)
Neopterin is a valuable diagnostic biomarker, which is elevated in inflammatory conditions like periodontitis, that is characterized by destruction of the supporting structures of the teeth. Among the biomarkers, neopterin occurs in body fluids, and acts as a diagnostic marker for present and future disease activity. Thirty female subjects with chronic periodontitis, mean age 50 years (40-60 years) were included in this study. Depending upon their menstrual history, subjects were categorized into two groups of fifteen each. Group I 15 pre-menopausal women, and Group II 15 post-menopausal women. Saliva was collected, and neopterin levels were assessed by enzyme-linked immunosorbent assay in both the groups, at base line and after three months of nonsurgical periodontal therapy (NSPT). Periodontal parameters like pocket probing depth (PD) and Russell's periodontal disease index (PDI) were assessed before treatment as well as after three months of scaling and root planning. Intra group analysis showed significant markdown in the mean values of all the parameters from baseline to three months ( < 0.001), for all patients. The intergroup comparison, from baseline to 3 months also showed no significant change in PD and PDI values, but there was a statistically significant difference in the salivary neopterin levels ( = 0.04). Neopterin levels were found to be reduced in three months after NSPT in both the groups, suggesting that the NSPT is the gold standard therapy, and also that neopterin levels in saliva can be used as an indicator to identify periodontal inflammation and destruction.